Anesthesia Health System Capacities in Public Hospitals of Punjab, Pakistan. - Shahbaz, Sumbal; Zakar, Rubeena; Fischer, Florian (Inquiry (00469580), 2021)
Purpose: This study intends to outline the capacity of anesthesia health system in public hospitals of Punjab, Pakistan. Methods: A cross-sectional survey among public hospitals of Punjab was carried out that provide emergency and elective surgical care. We measured capacity in terms of infrastructure; surgical, anesthetic, and obstetric (SAO) workforce; surgical interventions; information management; equipment; and medication which was accomplished between October 2020 and February 2021. Results: Out of 106 public hospitals in Punjab, almost 40% had only one anesthesia provider. Only 50% of the hospitals reported round the clock availability of anesthesia providers for surgical cases. While caesarean sections were carried out in more than 90% of health facilities, general surgery, pediatric surgery, and open fracture surgery were conducted only in 50% of the hospitals. Although local and general anesthetic agents were available in the majority of hospitals, essential medicines for safe anesthesia were not available in all hospitals. Conclusion: This first comprehensive assessment of anesthesia health system capacity exposed a crucial deficiency of critical supplies and workforce for providing safe anesthesia and, hence, safe surgery. The surveyed facilities had an uneven division of resources.